A dilemma for non-analytic naturalism - Forcehimes, Andrew T. (2019)
In recent years, an impressive research program has developed around non‐analytic reductions of the normative. Nevertheless, non‐analytic naturalists face a damning dilemma: either they need to give the same reductive analysis for epistemic and practical reasons, or they can give a different analyses by treating epistemic and practical reasons as a species of the larger genus, reasonhood. Since, for example, a desire‐based account of epistemic reasons is implausible, the reductionist must opt for the latter. Yet, if the desire‐based account of practical reasons is merely a species of the larger genus, then, due to a violation of irreflexivity, the reduction fails.